2014
DOI: 10.1038/leu.2014.112
|View full text |Cite
|
Sign up to set email alerts
|

PKA/AMPK signaling in relation to adiponectin’s antiproliferative effect on multiple myeloma cells

Abstract: Obesity increases the risk of developing multiple myeloma (MM). Adiponectin is a cytokine produced by adipocytes, but paradoxically decreased in obesity, that has been implicated in MM progression. Herein, we evaluated how prolonged exposure to adiponectin affected the survival of MM cells as well as putative signaling mechanisms. Adiponectin activates protein kinase A (PKA), which leads to decreased AKT activity and increased AMP-activated protein kinase (AMPK) activation. AMPK, in turn, induces cell cycle ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 54 publications
5
82
0
2
Order By: Relevance
“…Previous studies showed an inverse correlation between plasma concentration of adiponectin and incidence of breast, prostate, colorectal, and acute myeloid leukemia [9, 10, 13, 19]. Adiponectin is suggested to be a protective factor by exerting anti-inflammation, insulin-sensitizing, and anti-angiogenesis [2022]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed an inverse correlation between plasma concentration of adiponectin and incidence of breast, prostate, colorectal, and acute myeloid leukemia [9, 10, 13, 19]. Adiponectin is suggested to be a protective factor by exerting anti-inflammation, insulin-sensitizing, and anti-angiogenesis [2022]. …”
Section: Introductionmentioning
confidence: 99%
“…BM-adipocytes, the major source of serum adiponectin that increases during caloric restriction as well as during cancer therapy (37), has been shown to contribute to chemotherapy resistance via adipocyte-secreted adipokines and AMPK-dependent autophagy activation in myeloma cells (38). Our co-culture experiments conducted in serum-starved conditions also demonstrated adiponectin production by BM-adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloma cell apoptosis is decreased in myeloma-bearing adiponectin-deficient mice while increasing adiponectin via an apolipoprotein peptide mimetic L-4F increased myeloma cells apoptosis in vitro and in vivo, reduced myeloma tumor burden and prevented myeloma bone disease [82,107]. A very recent experimental study has shown that adiponectin's ability to enhance MM cell cycle arrest and apoptosis was attributed to the suppression of lipogenesis through the protein kinase A (PKA)/ AMPK-dependent decline of the enzyme expression acetyl-CoA-carboxylase (ACC), suggesting that ACC inhibitors or PKA/AMPK pathway activators could be used as therapeutic adjuvants in MM [108]. …”
Section: Adiponectin and MMmentioning
confidence: 99%